(untitled) (Research, Society and Development, 2022)
Absenteeism is a chronic healthcare problem worldwide in both the public and private sectors, leading to waste of financial resources. To estimate the rate and the waste of monetary resources linked to patient absenteeism in consultations and specialized examinations on the management modalities of the Brazilian Unified Health System (SUS) in the Metropolitan Health Region of the state of Espirito Santo (RSMES), from 2014 to 2016. A total of 1,002,719 procedures were analyzed, of which 666,182 were medical consultations and 336,537 were examinations scheduled in one of the 38 executing sites, being 7 from direct administration and 31 from indirect administration. Data were obtained from the administrative records of the Regulation System of the State of Espirito Santo (SISREG-ED. Monetary values were obtained from the SUS table, a complementary table of contracts and a table of estimated costs according to the type of service provider. For medical consultations, the highest rates and values wasted with absenteeism were found, in the private service 42.7% (R 2,000.00) and in the public 39.1% (R 2,255,320.00). For exams, in philanthropic 34.9% (R 4,459,951.03) and in the public with OSS management 32,4% (R 8,943,943.26) The amount of healthcare units, the production and the number of resources provided by the SUS for specialized examinations were mostly destined to indirect administrations, mainly the philanthropist and the public with health social organization providers. The rates of absenteeism and the wasted resources evidence the challenge in the SUS manager’s agenda.